The Effectiveness of Long-Term Rehabilitation Treatment After Stroke - Shirmen, Batchimeg; Oidov, Batgerel; Tsegmid, Naran; Bayartsogt, Batzorig; Guntev, Tsagaankhuu; Avirmed, Baljinnyam (Central Asian Journal of Medical Sciences, 2020)
Objectives: Stroke is the leading cause of long-term disability. Therefore, we studied the effects of comprehensive long-term rehabilitation after stroke in improving the quality of life. Methods: Participants were compared in an experimental intervention model, with 120 control subjects, which received conventional short-stay inpatient hospitalization rehab, with 105 study subjects who received comprehensive rehabilitation program using the Guidelines for Adult Stroke Rehabilitation and Recovery from the American Heart Association/American Stroke Association starting in the hospital and extending for 6 months. The effects of rehabilitation were assessed Modified Rankin Scale (mRS), Functional Independence Measure (FIM), Barthel Index (BI) methods at admission, discharge, and 3 and 6 months after discharge. Results: There was no significant difference in the NIHSS, mRS, BI, and FIM scores between study and control patients at admission (p > 0.05). For the mRS, BI, and FIM scores, there was a significant interaction between treatment and time, indicating that the scores improved more rapidly for patients in the study group than the control group over the six-month study period (p < 0.001). A significant improvement in the scores with time was observed in the study and control groups at each time interval (p < 0.001). However, by 3 months after discharge the mRS, BI, and FIM scores of the study group were significantly better than the control group and the gap widened at 6 months, indicating further improvement. Conclusions: We found that providing prolonged by a multidisciplinary rehabilitation team results in higher functional independence and improvements in daily living activities.